Taxes, Expenditure and Development Nexus: A Panel VECM Analysis on Romanian NUTS2 Regions - Surugiu, Marius; Surugiu, Camelia; Mazilescu, Raluca; Cristea, Anca (European Journal of Sustainable Development, 2021)
The investigation starts with the computation of the Socio-Economic Development Index (SEDI index) with data for Romania. Based on the index values, the long-run relationship between taxes and expenditure is assessed, for Romanian NUTS2 regions from 2000 to 2016. According to the results, there is a Granger causality relationship from budget revenue and expenditure to SEDI. The results emphasize the significant impact of taxes and expenditure on socio-economic development. The paper underlines the need for effective public strategies to be implemented by the authorities at the regional level, which may propel the socio-economic development. The results support the fiscal synchronization hypothesis.